Analisis kesulitan membaca siswa kelas II di SD Negeri Jakarta Timur - Sarah Titi Nabilah; Zulfadewina Zulfadewina (Curricula: Journal of Curriculum Development, 2026)
Reading ability is a fundamental skill that plays an important role in learning success in elementary school. However, in practice, some students still experience reading difficulties, particularly in the lower grades. This study aims to analyze the types of reading difficulties, the contributing factors, and the teachers’ efforts to overcome reading difficulties among second-grade students at SD Negeri Jakarta Timur. This research employed a descriptive qualitative approach. Data collection techniques included reading ability tests, observation, and documentation. The results showed that of 32 students, 26 were categorized as having good reading ability, while 6 were categorized as having low or very low reading ability. The reading difficulties identified included spelling difficulties, difficulty pronouncing and recognizing letters, letter substitution, insufficient attention to punctuation, poor memory retention, and long-distance vision problems. The factors influencing reading difficulties were internal student factors, learning materials, and the lack of parental assistance at home. Teachers’ efforts to address these difficulties included providing additional learning time, utilizing instructional media, giving motivation and appreciation, and fostering collaboration between teachers and parents.